Lab-on-a-Chip Fabrication and Application 2016
DOI: 10.5772/62865
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field-Based Technologies for Lab-on-a-Chip Applications

Abstract: In the last decades, LOC technologies have represented a real breakthrough in the field of in vitro biochemical and biological analyses. However, the integration of really complex functions in a limited space results extremely challenging and proper working principles should be identified. In this sense, magnetic fields revealed to be extremely promising. Thanks to the exploitation of external magnetic sources and to the integration of magnetic materials, mainly high aspect ratio micro-/nanoparticles, non-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The locomotion results are reported in figure 8. A clear linear correlation was found between the microrobot speed and the magnetic field gradient, thus confirming the theoretical considerations reported in equations ( 1) and (7). In addition the results demonstrated that the speed of the microbot moved on liquid is bigger than the speed of the microrobot moved on hydrogel.…”
Section: Magnetic Locomotion and Immersion Testssupporting
confidence: 87%
See 1 more Smart Citation
“…The locomotion results are reported in figure 8. A clear linear correlation was found between the microrobot speed and the magnetic field gradient, thus confirming the theoretical considerations reported in equations ( 1) and (7). In addition the results demonstrated that the speed of the microbot moved on liquid is bigger than the speed of the microrobot moved on hydrogel.…”
Section: Magnetic Locomotion and Immersion Testssupporting
confidence: 87%
“…In addition, the serial execution of routine tasks is fully dependent on human operators [5]. LOC systems could greatly benefit from the opportunity to move cells automatically or in a teleoperated manner, by exploiting microrobotic technologies in a microfluidic environ ment that may provide low contamination capability, high-throughput and repeatability with respect to manual handling [6,7]. Micro-object locomotion in 3D liquid-filled spaces is extremely challenging due to scaling effects: at small dimensions, static friction, adhesion and viscous forces play a major role and they have to be properly balanced in order to achieve an effective locomotion [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the integration of truly multifaceted functions in a very narrow space still remains challenging. NPs are an innovative option, allowing noncontact manipulation of physical, chemical, and biological samples …”
Section: Introductionmentioning
confidence: 99%
“…Magnetically patterned magnetic materials are promising media for various applications e.g., as high-density storage devices 1 4 , for spin wave propagation in magnonics 5 , 6 , and in lab-on-a-chip platforms 7 9 . During the last few decades, several techniques have been developed to locally modify the magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Using this approach, we created 2D heterostructures characterized by different combinations of magnetic properties in areas modified by plasma oxidation and in the regions protected from oxidation. As plasma oxidation is an easy to use, low cost, and commonly utilized technique in industrial applications, it may constitute an improvement over other magnetic patterning methods.Magnetically patterned magnetic materials are promising media for various applications e.g., as high-density storage devices 1-4 , for spin wave propagation in magnonics 5,6 , and in lab-on-a-chip platforms [7][8][9] . During the last few decades, several techniques have been developed to locally modify the magnetic properties.…”
mentioning
confidence: 99%